2019
DOI: 10.1177/1687814019835102
|View full text |Cite
|
Sign up to set email alerts
|

Comparing uncertainties in travel mode choice decisions for various trip chains

Abstract: The main purpose of this article is to compare the mode choice decisions between commuting and non-commuting trip chains and evaluate the uncertainties in the mode choice process. According to household survey data from a mediumsized city in China, the whole day of travel is divided into several types of travel chains. We used the multinomial logit model to estimate the impacts of factors on the choices of trip modes, which included walk, bike, public transit, and car. The entropy theory was introduced to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In practice, trip chaining studies use the multinominal logit model for modelling [11], while the bivariate ordered probit model [10] and ordered probit model [13,16] are also used. Regression analysis [12,25] has also been used for better insight into trip chaining behaviour and individuals' travel patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, trip chaining studies use the multinominal logit model for modelling [11], while the bivariate ordered probit model [10] and ordered probit model [13,16] are also used. Regression analysis [12,25] has also been used for better insight into trip chaining behaviour and individuals' travel patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, most studies agree that the formation of complex trip chains is related to socioeconomic, demographic and urban form characteristics [10][11][12][13]. Specific variables explored in the literature include household composition and life cycle stage, age, gender, marital status, income, employment status, car availability, residential density and density of transit stops.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…From another viewpoint, Wan et al (2019) found that the factors affecting the mode choice for commuting trips as not necessarily having the same impacts on choice behavior for non-commuting trips but they rather could have opposite effects and vice-versa. Moreover, Chen and Li (2017) combined the discrete choice model for public transportation (PT) services with another mathematical model: Structural Equation Model to enhance the accuracy of modal split outputs.…”
Section: Introductionmentioning
confidence: 99%